Effect of a pay-it-forward strategy on reducing HPV vaccine delay and increasing uptake among 15- to 18-year-old girls in China: A randomized controlled trial. - Jing Li; Yifan Li; Chuanyu Qin; Yu He; Haidong Lu; Yewei Xie; Jason J Ong; Yajiao Lu; Ying Yang; Fan Yang; Heng Du; Wenfeng Gong; et al. (PLoS Medicine)
Background Catch-up human papillomavirus (HPV) vaccination is challenging in many low- and middle-income countries (LMICs). Pay-it-forward offers an individual a subsidized vaccine, then an opportunity to donate to help others access vaccinations. Our randomized control trial assessed the effectiveness of pay-it-forward in improving HPV vaccination among girls aged 15-18 years in China. Methods and findings This study was conducted from July 6, 2022, to June 9, 2023, in four community health centers (CHCs) in Chengdu, western China. Eligible participants were unvaccinated girls living in the service areas of CHCs. Participants were initially recruited via telephone and, after providing verbal consent, attended in-person visit where they were randomly assigned using the sealed envelope method to either the pay-it-forward arm (received a community subsidy of 47.7 USD covering the first vaccine and an opportunity to support others) or control arm (self-paid vaccination at the market price). Participants were unblinded only after the envelope was opened, while the CHC staff coordinators, physicians prescribing the vaccine, outcome assessors, and data analysts were blinded to the intervention allocation. The primary outcome was the first-dose HPV vaccination rate, verified against clinical records. Data were analyzed using the intention-to-treat approach. We identified 662 participants per phone invitation. A total of 321 participants showed up in the health centers and randomly assigned to the pay-it-forward arm (n = 161) or control arm (n = 160). Most caregivers were female (80.1%, 257/321). In the pay-it-forward arm, 55 of 161 (34.2%) girls received the HPV vaccine, compared with 28 of 160 (17.5%) girls in the control arm (adjusted proportion difference = 17.9%, (95% CI [8.7%, 27.0%]; P < 0.001). Among 55 girls in the pay-it-forward arm who received the vaccination, 37 (67.3%) wrote a postcard message, and 39 (70.9%) of their caregivers donated to support future girls. The financial cost per person vaccinated was $294 in the control arm and $230 in the pay-it-forward arm. The trial had several limitations, including a 54% clinic attendance rate (360 of 662 consented participants attended) and its conduct in a single western province of China. Conclusions The pro-social pay-it-forward strategy was effective to increase catch-up HPV vaccination among teenage girls. This approach also enhanced vaccine confidence among participants. Pay-it-forward demonstrates promise as an effective intervention to improve vaccine uptake through community engagement. Trial registration Chinese clinical trial registry ChiCTR2200055542 (https://www.chictr.org.cn/hvshowproject.html?id=183292&v=1.3).